Discordant findings of different positron emission tomography/CT tracers in a case of glioblastoma - Kumar, Ram; Gupta, Nitin; Ranjan, Rajeev; Verma, Ritu; Belho, Ethel; Sen, Ishita (World Journal of Nuclear Medicine, 2021)
18F-2-fluoro-2-deoxy-D-glucose ([18F]-FDG) positron emission tomography (PET) CT has proven useful in the evaluation of high-grade glioma and is also useful as a predictor of the degree of malignancy in newly diagnosed brain tumors. It is commonly accepted that high-grade gliomas are characterized by increased FDG uptake, whereas the low-grade glioma demonstrates reduced or absent FDG uptake. [18F]-FDOPA is an amino acid PET tracer which is a marker of the proliferative activity of brain tumors and demonstrates positive uptake in all grades of brain tumors; however, the degree of tracer uptake is significantly higher in high-grade tumors as compared to low-grade tumors. Here, we discuss a case where both FDG and DOPA PET/CT scans raised suspicion of low-grade glioma; however, the final histopathology report confirmed WHO grade IV Glioblastoma.
Keywords: 18F-DOPA; 18F-2-fluoro-2-deoxy-D-glucose; dual tracer positron emission tomography; false-negative positron emission tomography/CT; high-grade glioblastoma